2008
DOI: 10.1111/j.1365-2109.2008.01944.x
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan as a wall material for a microencapsulated delivery system for Macrobrachium rosenbergii (de Man) larvae

Abstract: Chitosan has been widely accepted as a wall material for preparing microcapsules of various purposes in human medicine. The possibility of using chitosan as a wall material for microencapsulating nutrients and drugs for aquaculture purposes, specifically to Macrobrachium rosenbergii larvae was evaluated in this study. Two types of chitosan‐coated microcapsules were prepared using either acetone (MEC‐A) or NaOH (MEC‐N) as the cross‐linking agents. They were compared with a microbound diet relative to total leac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Mortality rates were reduced by 37% and 68% in the dsRNA-producing bacteria and dsRNA-chitosan nanoparticles—fed individuals, respectively. Anas et al [ 98 ] further characterized the properties of chitosan nanoparticles and concluded that they are suitable for encapsulating drugs for oral delivery into M. rosenbergii larvae. While this approach proved useful to some extent, only one very recent report has examined the option of using oral delivery to silence a gene systemically in crustaceans (summarized in Section 3.3 ).…”
Section: Study Of the Crustacean Innate Immune System Using Rnaimentioning
confidence: 99%
“…Mortality rates were reduced by 37% and 68% in the dsRNA-producing bacteria and dsRNA-chitosan nanoparticles—fed individuals, respectively. Anas et al [ 98 ] further characterized the properties of chitosan nanoparticles and concluded that they are suitable for encapsulating drugs for oral delivery into M. rosenbergii larvae. While this approach proved useful to some extent, only one very recent report has examined the option of using oral delivery to silence a gene systemically in crustaceans (summarized in Section 3.3 ).…”
Section: Study Of the Crustacean Innate Immune System Using Rnaimentioning
confidence: 99%
“…Microbound diet was also used as an alternative for larvae of Litopenaeus vannamei (D'Abramo, Perez, Sangha, & Puello-Cruz, 2006). Chitosan-walled microcapsule diet to know the morphology of capsule, leaching of total nutrients and free amino acids (FAA) and diet acceptance of Macrobrachium rosenbergii (Anas, Philip, & Singh, 2008). Gelatin-walled microcapsule diet was evaluated to know the retention of vitamin C, lipid encapsulation and nitrogen retention efficiency for Penaeus japonicus Bate (Xie et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…; Ozkizilcik & Chu ; Buchal & Langdon ; Baskerville‐Bridges & Kling ; Langdon ; Önal & Langdon ; Anas et al . ). Vitamin C is an example that was successfully preserved and delivered to rainbow trout via encapsulation (Alishahi et al .…”
Section: Applications Of Encapsulation Technology In Aquaculture – Camentioning
confidence: 99%
“…For instance, chitosan was successfully used to produce a microencapsulated diet for marine larvae (Anas et al . ). Low level of nutrient leaching (23.3%) and high acceptance rate of 75% were reported for chitosan‐walled microcapsules after feeding Macrobrahium rosenbergii larvae (Anas et al .…”
Section: Applications Of Encapsulation Technology In Aquaculture – Camentioning
confidence: 99%
See 1 more Smart Citation